2022
DOI: 10.1097/md.0000000000030794
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of adaptive NK cells are associated with absence of coronary plaque in cytomegalovirus infected people living with HIV

Abstract: The objective of this study was to evaluate whether adaptive NKG2C + CD57 + natural killer (adapNK) cell frequencies are associated with pre-clinical coronary atherosclerosis in participants of the Canadian HIV and Aging Cohort Study. This cross-sectional study included 194 Canadian HIV and Aging Cohort Study participants aged ≥ 40 years of which 128 were cytomegalovirus (CMV) + people living with HIV (PLWH), 8 were CMV − PLWH, 37 were CMV mono-infected individuals, and 21 were neither human immunodeficiency v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…NK cell numbers were also reported to decrease with inflamed carotid plaques relative to stable femoral plaques 43 . In a preclinical study of coronary atherosclerosis, adaptive NKG2C + CD57 + NK cells were associated with lower plaque volume, suggesting a protective function 19 . Interestingly, we found that the adaptive NK cell gene signature increased in the carotid, more inflamed, plaque tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cell numbers were also reported to decrease with inflamed carotid plaques relative to stable femoral plaques 43 . In a preclinical study of coronary atherosclerosis, adaptive NKG2C + CD57 + NK cells were associated with lower plaque volume, suggesting a protective function 19 . Interestingly, we found that the adaptive NK cell gene signature increased in the carotid, more inflamed, plaque tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive FcεRIγ − NK cells (g − NK cells) 16 exhibit reduced protein expression of the IL-2 receptor beta-chain (CD122, IL2RB ), and high expression of IL-32, CCL5, GZMH, and LAG3 10,17,18 . In a pre-clinical study of coronary atherosclerosis, adaptive NKG2C + CD57 + NK cells were associated with lower plaque volume, sug-gesting a protective function 19 . Nonetheless, there is limited data regarding the human NK cell gene ex-pression profile and subset differentiation in CAD and with respect to HCMV status and other risk fac-tors 20,21 .…”
Section: Introductionmentioning
confidence: 96%